2021
DOI: 10.1136/thoraxjnl-2021-216880
|View full text |Cite
|
Sign up to set email alerts
|

Does pay-for-performance improve patient outcomes in acute exacerbation of COPD admissions?

Abstract: BackgroundThe COPD Best Practice Tariff (BPT) is a pay-for-performance scheme in England that incentivises review by a respiratory specialist within 24 hours of admission and completion of a list of key care components prior to discharge, known as a discharge bundle, for patients admitted with acute exacerbation of COPD (AECOPD). We investigated whether the two components of the COPD BPT were associated with lower 30-day mortality and readmission in people discharged following AECOPD.MethodsLongitudinal study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
2
1
Order By: Relevance
“…Financial incentives often are seen as being an important element in changing clinical practice. 49 A recent study found that pay-for-performance as part of a health-care system initiative in England resulted in higher uptake in discharge bundle use compared with the current study (53% vs 19% in the current study); however, this discharge bundle was not associated with reduced readmission rates or mortality. 49 Further study in this area is warranted.…”
Section: Discussioncontrasting
confidence: 71%
“…Financial incentives often are seen as being an important element in changing clinical practice. 49 A recent study found that pay-for-performance as part of a health-care system initiative in England resulted in higher uptake in discharge bundle use compared with the current study (53% vs 19% in the current study); however, this discharge bundle was not associated with reduced readmission rates or mortality. 49 Further study in this area is warranted.…”
Section: Discussioncontrasting
confidence: 71%
“…The remains unexplained variation in care for COPD exacerbations, and national audit programmes such as the UK National Asthma and COPD Audit Programme can be used to benchmark care [15]. There is evidence that care is improved when patients with COPD are reviewed by a COPD specialist from the multi-disciplinary team during their admission [16].…”
Section: Respiratory Physiotherapy Techniques Can Be Valuable In Assi...mentioning
confidence: 99%
“…As defined by the Institute for Healthcare Improvement, a care bundle is “a small set of evidence based interventions for a defined patient segment/population and care setting that, when implemented together, will result in significantly better outcomes than when implemented individually” [ 100 ]. Care bundles have been demonstrated to improve the outcomes of COPD, especially when a respiratory specialist is involved [ 101 , 102 ].…”
Section: Introductionmentioning
confidence: 99%